THE LENGTH WEIGHT RELATIONSHIP AND CONDITION FACTOR OF SCHILBE MYSTUS AND PHYSICO CHEMISTRY OF WATER IN ZOBE DAM DUTSINMA, KATSINA STATE - Mzungu, I.; Orpin, J. B.; Amos, B. (FUDMA JOURNAL OF SCIENCES, 2023)
Length weight relationship and condition factor of Schilbe mystus and physicochemistry of water in Zobe dam in Dutsinma Katsina State was carried out. Twenty (20) Schilbe mystus species each were collected with water samples monthly for six (6) months making a total of one hundred and twenty (120) fish and six(6)water samples, morphometric measurement and physicochemical analysis was carried out using a meter rule and weighing balance. The results obtained showed that the growth pattern of the fish were negatively allometric with b values ranging from 2.161 and 2.842 obtained at p<0.05. There was strong correlation between the length and weight of the species with condition factor (k) as 0.72, an indication that the fishes were not doing very well in the dam. The physicochemical parameters analysed including temperature, turbidity, pH, conductivity and dissolve oxygen played a negative role in the condition factor of the fish species because it was observed that the water quality of the dam was very poor to aid survival of Schilbe mystus. More studies should be carried out on other species of fish found in Zobe dam to enhance proper management of the dam.